Live imaging of developmental processes in a living meristem of Davidia involucrata (Nyssaceae) - Jerominek, Markus; Bull-Hereñu, Kester; Arndt, Melanie; Claßen-Bockhoff, Regine (Frontiers in Plant Science, 2014)
Morphogenesis in plants is usually reconstructed by scanning electron microscopy and histology of meristematic structures. These techniques are destructive and require many samples to obtain a consecutive series of states. Unfortunately, using this methodology the absolute timing of growth and complete relative initiation of organs remain obscure. To overcome this limitation, an in vivo observational method based on Epi-Illumination Light Microscopy (ELM) was developed and tested with a male inflorescence meristem (floral unit) of the handkerchief tree Davidia involucrata Baill. (Nyssaceae). We asked whether the most basal flowers of this floral unit arise in a basipetal sequence or, alternatively, are delayed in their development. The growing meristem was observed for 30 days, the longest live observation of a meristem achieved to date. The sequence of primordium initiation indicates a later initiation of the most basal flowers and not earlier or simultaneously as SEM images could suggest. D. involucrata exemplarily shows that live-ELM gives new insights into developmental processes of plants. In addition to morphogenetic questions such as the transition from vegetative to reproductive meristems or the absolute timing of ontogenetic processes, this method may also help to quantify cellular growth processes in the context of molecular physiology and developmental genetics studies.